Propriedades ópticas não lineares em semicondutores bidimensionais e materiais biológicos - Lucas Lafetá Prates da Fonseca (2022)
This thesis addresses the applications of non-linear optics techniques in different materials. Above all, we approach the applications of second harmonic generation and four-wave mixing in two-dimensional materials, in this case of the transition metal dichalcogenides family. Also, we used Raman and Stimulated Raman spectroscopy techniques to identify beta-amyloid protein deposits in the brain of mice genetically modified to develop Alzheimer's disease. In the first case, we used second-harmonic generation, which is a second-order nonlinear optical effect, and four-wave mixing, a third-order phenomenon, to identify resonances with the excitons of MoS2, MoSe2, and WS2 monolayers. In addition, we measure and characterize the electrical susceptibility of these materials, inside and outside, to exciton resonance. These results were compared with experimental values ​​measured by different optical techniques available in the literature. In the case of biological materials, we studied the plaques formed by the accumulation of beta-amyloid in the brains of mice. In addition to conventional Raman measurements, to characterize the plates, we performed second harmonic generation, autofluorescence by two-photon excitation and fluorescence by two-photon excitation using markers, in order to observe the plates, in addition to determining their composition. . We also used stimulated Raman techniques, in this case, the SRS and CARS, in order to reduce the exposure time of the material in relation to the conventional Raman hyperspectral, in order to characterize the amyloid plaques in relation to specific Raman peaks. Based on the results of these different techniques, we were able to differentiate the animals by age using the principal component analysis technique. Another aspect of the study was to combine SRS analyzes with fluorescence measurements by two-photon excitation, labeling glial cells in order to differentiate the cells that participate in the formation of the amyloid plaque.